Nilai-Nilai Seni, Budaya, Dan Pendidikan Karakter Pada Cerita Rakyat Patih Sampun Asal Kabupaten Pemalang - Iin Turyani; Eko Sugiarto; Muh Fakhrihun Naam (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2024)
Folklore is not only part of a region's cultural heritage, but also carries moral messages that are valuable for character education. One of the folk tales that is rich in artistic values ​​and character education is the legend of Patih Sampun from Pemalang Regency. This article aims to explore and analyze the artistic, cultural and character education values ​​contained in these folk tales. The research method used is analysis of the Patih Sampun folklore text based on aspects of narrative art, character traits and the moral message conveyed. The results of the analysis show that Patih Sampun's folklore contains various artistic values, such as the use of distinctive language, depictions of nature and local culture, as well as interesting plot developments. Apart from that, Patih Sampun's character as the main character shows qualities such as courage, wisdom and loyalty, which is a good example for character formation for the younger generation. The meaning implied in this article includes the importance of using folklore as a learning resource to educate children's character. By understanding the values ​​of art and character education contained in the Patih Sampun folklore, educators can integrate the story into the character education curriculum at school. This will help strengthen local cultural identity and shape strong character and integrity in future generations.